2020
DOI: 10.1590/1678-4324-2020190702
|View full text |Cite
|
Sign up to set email alerts
|

Chia Seed Mucilage Versus Guar Gum: Effects on Microstructural, Textural, and Antioxidative Properties of Set-Type Yoghurts

Abstract: Texture is an important parameter which influences on the quality and acceptability of yoghurts. The utilize of stabilizers in yoghurt manufacturing has become a prevalent application to improve the textural properties of yoghurts. In this context, guar gum obtained from Cyamopsis tetragonolobus is generally used as a natural stabilizer for its thickening and gelling properties. Accordingly, this study evaluated the use of chia seed mucilage as an alternative to guar gum to improve the textural properties of y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 51 publications
0
5
0
1
Order By: Relevance
“…Aside from being a good texture stabilizer, improving the firmness and consistency of the yogurt, CM showed better antioxidant properties than guar gum. The potential of CM as a stabilizer in ice cream production was proven by the addition of 0.1-0.35 (w/w) freeze-dried CM replacing commercial stabilizer in ice cream [88]. These studies open the way for designing novel skimmed yogurts and desserts with higher fiber content based on CM.…”
Section: Application Of Plant-derived Mucilagementioning
confidence: 99%
See 1 more Smart Citation
“…Aside from being a good texture stabilizer, improving the firmness and consistency of the yogurt, CM showed better antioxidant properties than guar gum. The potential of CM as a stabilizer in ice cream production was proven by the addition of 0.1-0.35 (w/w) freeze-dried CM replacing commercial stabilizer in ice cream [88]. These studies open the way for designing novel skimmed yogurts and desserts with higher fiber content based on CM.…”
Section: Application Of Plant-derived Mucilagementioning
confidence: 99%
“…Consumers accepted the 7.5% addition of CM to yogurts, and rheological measurements confirmed that the fortified yogurts had better consistency, firmness, viscosity, and stress resistance compared with full-fat and skimmed yogurts [72]. Atik et al studied the effects of the application of chia mucilage on the technological, sensory, and microstructural properties of yogurts supported with CM or guar gum [88]. Aside from being a good texture stabilizer, improving the firmness and consistency of the yogurt, CM showed better antioxidant properties than guar gum.…”
Section: Application Of Plant-derived Mucilagementioning
confidence: 99%
“…In water, chia seeds can expand and produce a clear white mucus. Chia seeds are often also used as components in the manufacturing of certain food products and serve as thickeners, emulsifiers, or stabilizers [ 3 , 4 , 5 ]. Chia seeds have high fiber and protein contents, are gluten-free, high in omega-3 fatty acids, rich in vitamins and minerals, and contain antioxidants (polyphenols, tocopherols, and isoflavones) [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, increasing the water‐holding capacity and creating a gel increases the viscosity of yogurt, reduces syneresis, and improves the texture of yogurt (Atik et al, 2020 ). Adding guar gum to rice bran increases the moisture in the product due to its water retention power.…”
Section: Mechanisms Of Functionmentioning
confidence: 99%